Marker-assisted enhancement of bacterial blight (Xanthomonas oryzae pv. oryzae) resistance in a salt-tolerant rice variety for sustaining rice production of tropical islands - Gautam, Raj Kumar; Singh, Pankaj Kumar; Sakthivel, Krishnan; Venkatesan, K.; Rao, Shyam S.; Srikumar, M.; Vijayan, Joshitha; Rakesh, B.; Ray, Soham; Akhtar, Jameel; Meena, Bharat Raj; Langyan, Sapna; et al. (Frontiers in Plant Science, 2023)
Bacterial blight (BB) caused by Xanthomonas oryzae pv. oryzae is a major disease of rice, especially in the tropical regions of the world. Developing rice varieties with host resistance against the disease is the most effective and economical solution for managing the disease.Pyramiding resistance genes (Xa4, xa5, xa13, and Xa21) in popular rice varieties using markerassisted backcross breeding (MABB) has been demonstrated as a cost-effective and sustainable approach for establishing durable BB resistance. Here, we report our successful efforts in introgressing four resistance genes (Xa4, xa5, xa13 and Xa21) from IRBB60 to CARI Dhan 5, a popular salt tolerant variety developed from a somaclonal variant of Pokkali rice, through functional marker-assisted backcross breeding. Both BB and coastal salinity are among the major challenges for rice production in tropical island and coastal ecosystems. Plants with four, three, and two gene pyramids were generated, which displayed high levels of resistance to the BB pathogen at the BC3F2 stage. Under controlled salinity microplot environments, the line 131-2-175-1223 identified with the presence of three gene pyramid (Xa21+xa13+xa5) displayed notable resistance across locations and years as well as exhibited a salinity tolerance comparable to the recurrent parent, CARI Dhan 5. Among two BB gene combinations (Xa21+xa13), two lines, 17-1-69-334 and 46-3-95-659, demonstrated resistance across locations and years, as well as salt tolerance and grain production comparable to CARI Dhan 5. Besides salinity tolerance,